How I investigate bone marrow necrosis. (19th August 2019) - Deucher, Anne; Wool, Geoffrey D.
Abstract: Hematopathologists encounter bone marrow biopsy specimens with marrow necrosis relatively infrequently; when necrosis is seen, determining the clinical significance can be challenging. While bone marrow necrosis is not uncommon in site‐directed biopsy specimens or autopsy material, substantial necrosis is much less common in nondirected bone marrow biopsy specimens. Retrospective review showed the prevalence of bone marrow necrosis to vary between 0.3% and 2% antemortem, depending on the patient population. Numerous causes of bone marrow necrosis have been identified, including malignancy, radiation/chemotherapy, medication, infection, autoimmune disease, disseminated intravascular coagulation, antiphospholipid syndrome and other thrombotic disorders, granulocyte‐colony stimulating factor (G‐CSF) exposure, and hemoglobinopathies. Clinical findings associated with bone marrow necrosis include bone pain and fever, cytopenias, elevated LDH and ferritin, and leukoerythroblastosis. Rarely, such as in fat embolization syndrome (FES), bone marrow necrosis can be associated with thrombotic microangiopathy, neurologic dysfunction, and multiorgan failure. A thorough review of the patient's clinical record (including medical history, clinical presentation, and other laboratory findings), a thorough morphologic review of the bone marrow with appropriate ancillary stains, and an appreciation of the causes of bone marrow necrosis in different patient populations are required to determine the underlying cause of bone marrow necrosis. The purpose of this review is to present a strategy for evaluation of bone marrow necrosis found in an antemortem biopsy specimen.